Evolution of cosmic ray electron spectra in magnetohydrodynamical simulations - Winner, Georg; Pfrommer, Christoph; Girichidis, Philipp; Pakmor, Rüdiger (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. Cosmic ray (CR) electrons reveal key insights into the non-thermal physics of the interstellar medium (ISM), galaxies, galaxy clusters, and active ga